The Great Wall - Mann, Elizabeth, 1948-; Witschonke, Alan, 1953- (1997)
Examines the building of the Great Wall of China and the thousands of years of conflict that preceded it.
"The story of thousands of miles of earth and stone"--Cover.
Includes index.
Reading Counts RC
Accelerated Reader AR
Keywords: Great Wall of China (China) -- Juvenile literature; China -- History; Geschichte -- 475 v. Chr.-1912; Great Wall of China (China) -- History; Great Wall of China (China) -- Juvenile literature; Juvenile works; Children's nonfiction; Literature